Edible Pickering emulsion stabilized by protein fibrils. Part 1: Effects of pH and fibrils concentration. (March 2017) - Gao, Zhiming; Zhao, Junjun; Huang, Ying; Yao, Xiaolin; Zhang, Ke; Fang, Yapeng; Nishinari, Katsuyoshi; Phillips, Glyn O.; Jiang, Fatang; Yang, Hao
Abstract: Anisotropic particles exhibited unique interfacial properties, but only limited types of these particles are available for the food industry. Protein fibrils as anisotropic particles were surface active and expected to function in food systems. For this purpose, we utilize dialyzed and lyophilized β -lactoglobulin ( β -Lg) fibrils to fabricate stable oil-in-water Pickering emulsions at different fibrils concentrations and pHs. Our results demonstrated that β -Lg fibrils were able to stabilize oil-in-water emulsion as observed by fluorescence microscopy. The average droplet size ( d 3, 2 ) of the formed emulsions was between 11.0 and 19.0 μm, when homogenized with Ultra Turrax homogenizer at 20, 000 rpm for 2 min. The formed emulsions showed an excellent physical stability, which did not coalesce during 56 days storage under ambient temperature, at appropriate fibrils concentrations (5 mg/mL-20 mg/mL) and pHs far from the pI of β -Lg fibrils. At pHs near to its pI (pH 5.2) or with excessive fibrils concentration (≥25 mg/mL), fibrils tended to aggregate, resulting in coarse emulsions with large droplet size. Graphical abstract: Highlights: β -Lg fibrils can be used solely as an edible oil-in-water Pickering emulsion stabilizer. Emulsions stabilized by β -Lg fibrils have excellent physical stability which doesn't coalesce during long-term storage. Appropriate pH value and fibrils concentration are necessary for the formation and stability of the emulsions. Fluorescence microscope, SEM, and optical microscope were used to investigate the emulsion microstructure.